The New Global Rulers : The Privatization of Regulation in the World Economy - Büthe, Tim; Mattli, Walter (Book collections on Project MUSE., 2011)
Over the past two decades, governments have delegated extensive regulatory authority to international private-sector organizations. This internationalization and privatization of rule making has been motivated not only by the economic benefits of common rules for global markets, but also by the realization that government regulators often lack the expertise and resources to deal with increasingly complex and urgent regulatory tasks. The New Global Rulers examines who writes the rules in international private organizations, as well as who wins, who loses--and why.